The effect of climate on the physiological comfort of humans in the Alzawiyah area (Journal of Libya for geographical studies, 2024)
The study of applied climate is one of the important fields in determining the characteristics of the influence that climate elements, collectively or individually, have on one or more natural or human phenomena.The current study came as a specification of the role played by climatic elements in determining the level of physiological comfort of a person in the Alzawiyah area, because of their direct impact on his feeling of comfort or distress, as the variation in climate elements during the months and seasons of the year leads to a variation in a person’s feeling of comfort from one season to another.
Keywords: Physiological comfort; heat; humidity; wind